2020
DOI: 10.1532/hsf.3163
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Preoperative Hypoalbuminemia, Blood Urea Nitrogen and Creatinine Levels on Postoperative Atrial Fibrillation on Off-Pump Coronary Bypass Surgery Patients

Abstract: Background: Postoperative atrial fibrillation (PoAF) is one of the most common complications to occur after open heart surgery. It has been shown that hypoalbuminemia accompanies some cardiovascular disorders. The present study evaluates the effects of pre-procedural albumin, blood urea nitrogen (BUN), and creatinine levels on PoAF. Methods: The data of 81 patients who underwent off-pump coronary artery bypass graft (CABG) surgery was evaluated. Patients who developed atrial fibrillation (AF) in the first 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…In a study by Yayla et al [14], albumin levels were found to be significantly lower in patients who developed saphenous vein occlusion after CABG operations. In other studies, significant correlations were found between atrial fibrillation developing after cardiac surgery and low albumin [15,16]. In our study, we found that albumin levels at the time of pneumonia diagnosis were low in patients who developed mortality, although it was not statistically significant (p = 0.076).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In a study by Yayla et al [14], albumin levels were found to be significantly lower in patients who developed saphenous vein occlusion after CABG operations. In other studies, significant correlations were found between atrial fibrillation developing after cardiac surgery and low albumin [15,16]. In our study, we found that albumin levels at the time of pneumonia diagnosis were low in patients who developed mortality, although it was not statistically significant (p = 0.076).…”
Section: Discussioncontrasting
confidence: 47%
“…This value is an important parameter indicating the state of dehydration in individuals and has been associated with poor clinical outcomes in patients with heart failure and pneumonia [9,17]. In a study by Akgül et al [16], a significant relationship was found between the development of postoperative atrial fibrillation, which is closely related to inflammation, and high BUN values after CABG operations. In our patients, BUN values at the time of diagnosis of pneumonia were significantly higher in the mortality group (p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 395 patients with stage 3 to 5 chronic kidney disease reported that enlarged LA diameter and hypoalbuminemia were independent predictors of the deterioration of renal function assessed by estimated glomerular filtration rate (eGFR) [ 42 ]. Akgul et al [ 43 ] recently reported that patients with postoperative atrial fibrillation (PoAF) had higher BUN and Cr compared to the PoAF(−) group. They suggested that BUN and Cr levels were predictors of postoperative atrial fibrillation after off-pump cardiopulmonary bypass grafting surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Due to age-related physiological changes and the effect of anemia, these patients may be more susceptible to hypoxia. Preoperative low albumin was reported to be a risk factor for the development of postoperative atrial fibrillation in elderly patients with off-pump cardiac surgery [17] . Another study suggested that low hemoglobin and albumin scores were not associated with postoperative atrial fibrillation, ventricular fibrillation, or asystole [11] .…”
Section: Discussionmentioning
confidence: 99%